Relativity : opposing viewpoints - Swisher, Clarice, 1933- (San Diego, Calif. : Greenhaven Press, 1990)
Explores Einstein's theory of relativity, its initial reception as well as current scientific acceptance of his ideas about time and space, and the mysterious workings of our universe.
Includes bibliographical references and index.
Wilson's Junior High School.
7.5
7.5
5-8.
5-8
Keywords: Einstein, Albert, -- 1879-1955.; Einstein, Albert, -- 1879-1955.; Cosmology -- Juvenile literature; Relativity (Physics) -- Juvenile literature; Cosmology; Relativity (Physics); Relativity (Physics); Universe